Awareness and usage of promotional tools by Lekor Shop's consumers / Sharifah Norherlini Syed Harun - Syed Harun, Sharifah Norherlini (Faculty of Business and Management, 2007)
Sales promotion is very important to many organizations. A good sales promotion may promise a good feedback from the customers towards the products and services offered. This project paper is to assess sales promotion strategies done by Lekor Shop. The objective of this research is to investigate the effect of sales promotion tools such as coupon, price discount, free sample, bonus pack and in store display on product trial among consumers of Lekor Shop. In getting relevant data, 40 questionnaires were distributed to the selected respondents. The respondents are the consumers of Lekor Shop at Shah Alam, Selangor. Data collected were analyzed by using Statistical Package for Social Science (SPSS) program. The analysis includes the frequency and correlation. Several limitations were faced in completing in this study. The sampling size is small compared to actual populations of Lekor Shop's consumers. Therefore, to obtain the correct sample size may required more times and effort which is beyond researcher capabilities and time frame given. Thus, recommendations are included in this project paper in order to help Lekor Shop to increase the effectiveness of the sales promotion strategies and create consumer awareness towards the product trial.